KETERGANTUNGAN MASYARAKAT PERBATASAN INDONESIA KEPADA MALAYSIA (STUDI KASUS : DESA BADAU, KECAMATAN BADAU, KABUPATEN KAPUAS HULU, KALIMANTAN BARAT) - Sari, Intan Permata (Institut Agama Islam Bengkulu, 2016)
Issues concerning border areas are an interesting issue, especially when President Joko Widodo focuses on developing the 3 T (Outermost, Outermost, and Underdeveloped) region. So far, the border area has only been used as a fringe area that is not interesting to be studied. There is little attention given by the government to the border area because it is constrained by cost and not a priority of government development. Therefore, the border community can not depend its fate on the Indonesian government and exploit the ease of access to neighboring countries. This causes the level of dependence of Indonesian society on the border so great to neighboring countries. They are 'forced' to be able to live in the midst of limited and limited access and facilities. Almost all communities in the border region experienced similar things, including the Badau community in West Kalimantan. Keywords: border areas, dependency, Badau, Kapuas Hulu, West Kalimantan, Indonesia, Malaysia, Lubok Antu